Bermain-main dengan Aturan Keluar Batas Negara: Praktik dan Perlawanan Warga Perbatasan terhadap Upaya Pendisplinan di Desa Aji Kuning - Ade Prasetya Cahyadi (Jurnal Sosiologi Andalas, 2023)
The people of Aji Kuning have a high dependence on the Malaysian state, especially regarding employment and the fulfillment of basic needs. In the midst of these conditions, the Government actually made efforts to discipline citizens who wanted to enter and exit the country's borders. Elaborating biopolitical theory from Michael Foucault and resistance theory from James Scott, this article analyzes efforts to discipline the body (biopolitics) of residents in the border areas and the responses that arise to these conditions. This research applies qualitative ethnographic research with the unit of analysis of residents in the Aji Kuning Village. The results showed that the body discipline (biopolitics) efforts were carried out using two practices at once. First, discipline through internalization of understanding of the subject to further increase nationalism (the love of the homeland). Second, the discipline carried out by institutions and civil apparatus is under state control, and is accompanied by several regulations. The response that appears to the disciplinary efforts is that citizens fight by playing with the rules outside the country's borders. The form of resistance is divided into two, namely (1) hidden resistance (hidden transcript) is carried out by passing through rats (illegal), circumventing the applicable rules, and having two citizenship statuses. (2) Open resistance (public transcript) shall be carried out by swearing annoyance and protest against the rules outside the country's borders which are considered too strict such as the difficulty of activating dead passports and the number of corrupt officers.